Introducing the Nusatupe innovation hub – showcasing the best of the sustainable island food systems - Palmer, Neil; Eriksson, Hampus; Wate, Jillian Tutuo; Bennet, Gregory; Saeni-Oeta, Janet (WorldFish, 2025)
It must be one of the most unusual and remote research outposts within CGIAR: The Nusatupe innovation hub inhabits the southwestern corner of the tiny coral atoll of Nusatupe, in Western Province, Solomon Islands. Surrounded by aquamarine waters, and with a Marine Protected Area close by, Nusatupe has been the site of a WorldFish research station for 40 years or so – remote from the rest of the world but very close to the lives of Solomon Islanders. Its recent transformation from a research station into an innovation hub is part of a much needed reinvention of the facility, to ensure it is responsive to the needs of local institutions, fishers, farmers and youth. It now undertakes and showcases a range of activities from coral replanting to fish preservation and handling, to indigenous food gardens, bringing in visitors from around Solomon Islands to show what nutritious, sustainable island food systems can look like.